Zhukovska A. Tacesic constituent as a part of the multicomponent nonverbal module: the principles of combination - Zhukovska A. (Philological Treatises, 2020)
The article deals with the study of the character’s touch behavior in the contemporary English language fictional discourse from the modular perspective. The tacesic module is defined as a structural part of the English fictional discourse which contains one or more nominative units designating touch. The analysis of the principles governing the combination of the tacesic module with other nonverbal modules results in the conclusion that at least three factors influence the modes they are combined within the frame of the multicomponent nonverbal module. They are the factors of directivity, harmony and equilibrium. In the English fictional discourse the character’s nonverbal signals can be directed at either one or more than one communicative partners. In the first case the directivity factor results in the appearance of the single-vectored multicomponent nonverbal module while the second case gives rise to the differently vectored one. The harmony factor can also be realized in at least two ways, i.e. the consonance and dissonance of the nominative units designating different nonverbal components, including touch. The equilibrium factor predetermines the inverse relationships between the nonverbal constituents of the multicomponent nonverbal module.